Corporate Social Responsibility dan Kinerja Keuangan: Pandemi Covid 19 Sebagai Variabel Moderasi - Effendy, Lukman; Isnaini, Zuhrotul; Isnawati, Isnawati (Universitas Mataram, 2024)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on financial performance and the moderating effect of the COVID-19 pandemic on the relationship between CSR and financial performance. The sample for this study was determined using purposive sampling with the criterion of manufacturing companies that disclose CSR. The sample size in this study is 524 company-years. The analysis was conducted using Moderated Regression Analysis with STATA 17 software. The results show that CSR has a positive effect on financial performance, and the COVID-19 pandemic does not moderate the relationship between CSR and financial performance.